2018
DOI: 10.1021/acs.jmedchem.8b00224
|View full text |Cite
|
Sign up to set email alerts
|

Novel Hybrid Conjugates with Dual Suppression of Estrogenic and Inflammatory Activities Display Significantly Improved Potency against Breast Cancer

Abstract: In this work, we developed a small library of novel OBHS-RES hybrid compounds with dual inhibition activities targeting both the estrogen receptor α (ERα) and NF-κB by incorporating resveratrol (RES), a known inhibitor of NF-κB, into a privileged indirect antagonism structural motif (OBHS, oxabicycloheptene sulfonate) of estrogen receptor (ER). The OBHS-RES conjugates could bind well to ER and showed remarkable ERα antagonistic activity, and they also exhibited excellent NO inhibition in macrophage RAW 264.7 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 61 publications
2
35
0
Order By: Relevance
“…Ning et al developed dual targeting conjugates by joining Res and oxabicycloheptene sulfonate (OBHS), a structural motif of estrogen receptor (ER), with the aim of suppressing estrogenic and anti-inflammatory activities in breast cancer cells (MCF-7) [ 52 ]. The rationale of this design was inspired by evidence that ER/NF-κB interactions are implicated in the progression of breast cancer [ 79 , 80 ].…”
Section: Hybrid Compounds Containing Curcumin and Resveratrolmentioning
confidence: 99%
See 4 more Smart Citations
“…Ning et al developed dual targeting conjugates by joining Res and oxabicycloheptene sulfonate (OBHS), a structural motif of estrogen receptor (ER), with the aim of suppressing estrogenic and anti-inflammatory activities in breast cancer cells (MCF-7) [ 52 ]. The rationale of this design was inspired by evidence that ER/NF-κB interactions are implicated in the progression of breast cancer [ 79 , 80 ].…”
Section: Hybrid Compounds Containing Curcumin and Resveratrolmentioning
confidence: 99%
“…The most potent compound was found among the type II series and showed remarkable stereospecific binding to ER, excellent NO inhibition in macrophage RAW 264.7 cells, and cytotoxicity in the low micromolar range against MCF-7 cells ( Figure 16 ). In vivo experiments, performed in xenograft models of nude mice injected with MCF-7 cells, showed that this hybrid is more potent than reference tamoxifen [ 52 ].…”
Section: Hybrid Compounds Containing Curcumin and Resveratrolmentioning
confidence: 99%
See 3 more Smart Citations